2016
DOI: 10.1016/j.celrep.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Resistance to an Inhibitor of Chromosomal Instability in Human Cancer Cells

Abstract: Summary Karyotype diversity is a hallmark of solid tumors that contributes to intratumor heterogeneity. This diversity is generated by persistent chromosome mis-segregation associated with chromosomal instability (CIN). CIN correlates with tumor relapse and is thought to promote drug resistance by creating a vast genomic landscape through which karyotypically unique clones survive lethal drug selection. We explore this proposition using a small molecule (UMK57) that suppresses chromosome mis-segregation in CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 33 publications
(46 reference statements)
12
64
1
Order By: Relevance
“…This concept was also echoed in the study described previously using small-molecule inhibitors to reduce CIN caused by deviant microtubule dynamics where treated cell populations became specifically desensitised to Aurora B inhibitors (Orr et al 2016).…”
Section: Evolutionary Trapsmentioning
confidence: 82%
See 1 more Smart Citation
“…This concept was also echoed in the study described previously using small-molecule inhibitors to reduce CIN caused by deviant microtubule dynamics where treated cell populations became specifically desensitised to Aurora B inhibitors (Orr et al 2016).…”
Section: Evolutionary Trapsmentioning
confidence: 82%
“…Furthermore, this study was performed in the absence of chemotherapy treatment, and it would therefore be very interesting to extend these studies to examine the response to chemotherapy of such 'CIN-limited' tumours. A similar approach to limit CIN driven by aberrant microtubule dynamics was recently taken by the use of a drug to potentiate MCAK, the molecular motor that depolymerises MTs and overexpression of which can limit CIN caused by hyperstable microtubules (Orr et al 2016). However, in this interesting study, the hypothesis of whether limiting CIN might impact tumour progression was unable to be tested due to the unexpected adaptation of CIN cancer cells to the agent, resulting in the re-establishment of high rates of chromosome mis-segregation.…”
Section: Modulating Cin Levels In Cancer For Therapeutic Benefitmentioning
confidence: 99%
“…Moreover, it is unclear whether these effects could be harnessed for a chemopreventive or therapeutic strategy. One recent study found that cancer cells are adept at ‘re-tuning’ CIN to optimal levels (10), so pharmacologic manipulation of CIN may be a challenge. Nevertheless, Sansregret et al have demonstrated that relatively minor delays in mitosis due to APC/C inhibition can substantially reduce CIN, and that APC/C mutations found in cancer reduce its activity.…”
mentioning
confidence: 99%
“…In addition, we use a centromere antibody that marks the site of microtubule attachment to chromosomes to distinguish whole chromosomes lagging in anaphase from acentric DNA fragments, which contribute to structural aneuploidies. We typically use anti-centromere antibody (ACA) serum that contains antigens to multiple different centromere epitopes and is obtained from patients with autoimmune diseases (Orr, Talje, Liu, Kwok, & Compton, 2016). However, there are commercially available centromere antibodies as well (e.g.…”
Section: Immunofluorescence Assay For Lagging Chromosomes In Anaphasementioning
confidence: 99%
“…We have performed this assay using a variety of mammalian tissue culture cells, and there is no requirement for specific culture conditions or culture media (Orr et al, 2016; Thompson & Compton, 2008). …”
Section: Chromosome Mis-segregation Assaymentioning
confidence: 99%